2010
DOI: 10.1007/s00384-010-0993-7
|View full text |Cite
|
Sign up to set email alerts
|

Seton drainage prior to transanal advancement flap repair: useful or not?

Abstract: IntroductionTransanal advancement flap repair (TAFR) provides a useful tool in the treatment of high transsphincteric fistulas. Recent studies indicate that TAFR fails in one out of three patients. Until now, no definite predictive factor for failure has been identified. Although some authors have reported that preoperative seton drainage might improve the outcome of TAFR, this could not be confirmed by others. We conducted the present study to assess the influence of preoperative seton drainage on the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 16 publications
0
28
0
9
Order By: Relevance
“…The value of a Seton drain has not been definitively agreed. Current publications [30][31][32], some of which are the subject of lively debate, do not indicate that placement of a Seton drain represents an advantage for successful plastic fistula closure.…”
Section: Surgical Indicationmentioning
confidence: 95%
“…The value of a Seton drain has not been definitively agreed. Current publications [30][31][32], some of which are the subject of lively debate, do not indicate that placement of a Seton drain represents an advantage for successful plastic fistula closure.…”
Section: Surgical Indicationmentioning
confidence: 95%
“…Early case series suggested efficacy in around 70% of patients [132][133][134][138][139][140][141][142][143][144]. However, more recent randomized controlled trial data, often vs the anal fistula plug, and larger series, suggest healing in a smaller proportion, perhaps of the order of 50-60% [145][146][147]. A recent multicentre randomized trial of 94 patients from Scandinavia found a primary success rate (defined as clinical healing), at a median of 12 months of follow-up, of 62% of 40 patients.…”
Section: Fistula Recurrence After Advancement Flap Proceduresmentioning
confidence: 99%
“…There are many proponents of loose seton procedure stating that this technique should be the gold standard in patients with a history of pelvic radiotherapy, recurrent fistulas, Crohn's disease, fistulas involving more than 50% of the external sphincter, multiple fistula tracts and complicated fistulas such as horseshoe fistula [10]. However, there is inadequate data on the effectiveness, patient tolerance and follow-up period of this treatment [11]. In our study, there were patients with horseshoe fistula, Crohn's disease and transsphincteric and multiple fistula tracts (Figure 1: Multiple Fistula Tracts, Figure 2: Opening Of Multiple Fistula Tracts).…”
Section: Discussionmentioning
confidence: 99%